Holy Synod and Political Crisis of Interregnum - M. S. Belousov; T. V. Lebenkova (Научный диалог)
The features of the development of the dynastic crisis of the interregnum of 1825 through the prism of the functioning of one of the key public authorities - the Holy Synod is discussed in the article. An analysis of the literature allows us to conclude that in modern historiography, the events of the oath to Grand Duke Konstantin received conflicting estimates. It is noted that as a result there were several interpretative schemes of what happened in the capital on November 27. An appeal to the workflow of the Synod makes it possible to assert that from the point of view of the logic of the functioning of the state apparatus, a coup d’etat took place. An analysis of everyday activities, the key bureaucratic formulas in the protocols leads to the conclusion that the bureaucratic reaction to the oath to Konstantin did not correspond to the established traditions and was distinguished by haste and internal contradictions. This was reflected primarily in the decisions of November 27: the Synod decides on the oath, relying on oral reports from the synodal members, but the next day duplicates its own decision, referring to the jurisdiction of the Senate. Moreover, a comparison with the events of December 12-14 shows that the accession to the throne of Nikolai Pavlovich was carried out in accordance with the order established in the previous century and was distinguished by deliberate legal accuracy and consistency.